Implementasi Anggaran Berbasis Kinerja di Pemerintah Daerah dengan Akuntabilitas Kinerja “A” - Sofyani, Hafiez; Prayudi, Made Aristia (Jurnal Ilmiah Akuntansi dan Bisnis, 2018)
This study aims to examine the relationship several variables, namely: implementation of performance-based budgeting, budget absorption, accountability, and the use of performance information in formulating future planning and budgeting. The studywas organized in Provincial Local Government which the performance title “A” namely Daerah Istimewa Jogjakarta, using all of the Regional Working Unit (SKPD) as a research object. The respondents of the study are SKPDs officials directly involved in the formulation of planning and budgeting, as well as reporting the performance accountability of SKPD. Out of the 150 questionnaires distributed, only 97 are filled in completely and testable. Hypothesis testing employs Structural Equation Model (SEM) approach. The results show that performance-based budgeting is positively associated with budget absorption and SKPD’s accountability. In addition, good accountability also makes the local government apparatus triggered to use accountability reports as a reference in formulating plan and budget for the next period.   Keywords: Local government, performance-based budget, budget absorption, accountability, use of performance information